Efficient Bisphenol-A detection based on the ternary metal oxide (TMO) composite by electrochemical approaches. (20th August 2017) - Ahmed, Jahir; Rahman, Mohammed M.; Siddiquey, Iqbal A.; Asiri, Abdullah M.; Hasnat, Mohammad A.
Graphical abstract: Highlights: Ternary metal oxides (TMO) composites prepared by wet-chemical method. Highly sensitive and selective Bisphenol A (BPA) sensor by I–V method. Ultra-low detection limit was obtained by 3N/S. Real environmental samples were analyzed. Health care and environmental safety Abstract: A facile wet chemical method in basic medium was used to synthesis the ternary metal oxides (TMO; ZnO.CoO.FeO) composites at low temperature. The calcined TMO was characterized by FESEM, EDS, UV/vis., FTIR spectroscopy, EIS, and XRD systematically. Glassy carbon electrode (GCE) was modified with the TMO using 5% Nafion at room conditions. The resultant electrode was used for selective detection of Bisphenol-A (BPA) using cyclic voltammetry (CV). It was observed that the TMO electrode exhibited an excellent sensitivity (3.28 μAμM −1 cm −2 ), low detection limit (LOD: 1.2 ± 0.1 nM; S/N = 3), higher stability, very good repeatability, and reproducibility. In diagnostic exploration, a linear calibration plot was obtained for a wide range of concentration of BPA (LDR: 0.80 to 7.20 μM; r 2 : 0.99). This method represents an efficient way of sensitive sensor development for the detection of toxic and carcinogenic phenolic compounds.